Navier-Stokes/Darcy coupling: modeling, analysis, and numerical approximation - Marco Discacciati; Alfio Quarteroni (2009)
This paper is an overview of known and new results about the coupling of Navier-Stokes and Darcy equations to model the filtration of incompressible fluids through porous media. We discuss coupling conditions and we analyze the global coupled model in order to prove its well-posedness and to characterize effective algorithms to compute the solution of its numerical approximation.